Impact of Different Chronic Obstructive Pulmonary Disease Clinical Phenotypes on Quality of Life - Sumastika, Mos (Universiti Malaysia Sarawak (UNIMAS), 2021)
Chronic obstructive pulmonary disease (COPD) phenotype refers to a sole or mixture of disease features that explain the distinctions separating each individual with COPD based on clinically relevant criteria. The Spanish Society of Pulmonology and Thoracic Surgery phenotypes COPD predicated on the exacerbation frequency and dominant symptoms. In this study, the assessment on the effects of various COPD clinical phenotypes on patients’ health-related quality of life (HRQoL) was conducted. A cross-sectional study looking into COPD patients was carried out at the attending ambulatory clinics Serian Divisional and Bau District Hospitals from 23rd January 2018 to 22nd January 2019. Patients’ HRQoL were appraised utilising validated questionnaires such as the COPD Assessment Test (CAT), and St. George’s Respiratory Questionnaire for COPD (SGRQ-c). From 185 eligible respondents, n=108 (58.4%) were non-exacerbators (NON-AE), n=51 (27.6%) were frequent exacerbators (AE), and the remaining n=26 (14.1%) had asthma-COPD overlapped (ACO). Respondents with AE were found with chronic bronchitis with total of n=42 (82.4%), while remaining n=9 (17.6%) had emphysema. The total CAT and SGRQ-c scores were remarkably distinct between the COPD clinical phenotypes (all p < 0.001). The total CAT was crucially elevated in AE patients compared to ACO (17.3 ± 9.5 against 11.7 ± 8.6, p = 0.003) and NON-AE (17.3 ± 9.5 against 5.5 ± 4.7, p < 0.001). While for ACO, the CAT scores were markedly elevated against those with NON-AE (11.7 ± 8.6 against 5.5 ± 4.7, p < 0.001). The total SGRQ-c scores were crucially elevated in AE patients compared to ACO ((53.5 ± 22.7% against 34.4 ± 19.5%, p < 0.001) and NON-AE (53.5 ± 22.7% against 16.4 ± 14.8%, p < 0.001). ACO patients’ SGRQ-c scores were also markedly elevated against those with NON-AE (34.4 ± 19.5% against 16.4 ± 14.8%, p < 0.001). In subgroup analysis, the score for CAT item 3, 4, 5, 6 and 8 were remarkably higher for AE when compared with NON-AE (all p < 0.001), and ACO (p = 0.003 – 0.016). As for ACO against NON-AE, all iv the CAT items were prominently higher except CAT item 2 (p = < 0.001 – 0.040). All SGRQ-c components were also crucially higher for AE patients when compared with NON-AE (all p < 0.001), and ACO (p = < 0.001 – 0.005). Excluding Activity component in SGRQ-c, patients with ACO’s markedly higher in the rest of SGRQ-c’s component (p < 0.001) against NON-AE. To sum up, COPD patients’ HRQoL were indeed impoverished than the normal subjects irrespective of the clinical phenotypes. The poorest HRQoL is AE patients, then ACO and NON-AE . This study supports the recommendation to phenotype COPD patients based on the exacerbation frequency and COPD subtypes, therefore enabling personalisation and prioritisation of COPD management to achieve a better outcome and leading to an improve quality of life.